Biosourced Ligands from Isosorbide for the Ethylation of Aldehydes or Alkynylation of Imines. Issue 10 (8th August 2016) - Huynh, Khanh‐Duy; Ibrahim, Houssein; Bouchardy, Lucie; Bournaud, Chloée; Kolodziej, Emilie; Toffano, Martial; Vo‐Thanh, Giang
Abstract: β‐Amino alcohol and diamine ligands were prepared from isosorbide as a chiral renewable resource. The efficiencies of these ligands were evaluated for the metal‐catalyzed enantioselective ethylation of aldehydes and the alkynylation of aldimines. Abstract : The efficiencies of isosorbide‐derived β‐amino alcohol and diamine ligands were evaluated for the metal‐catalyzed ethylation of aldehydes and the alkynylation of aldimines. Good yields and up to 80 % ee were observed.